Differential expression of microRNAs in thymic epithelial cells from Trypanosoma cruzi acutely infected mice: putative role in thymic atrophy - Lacerda, Leandra Linhares (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisa sobre o Timo. Rio de Janeiro, RJ, Brasil.